Spectrophotometric Study of Photo-electro-catalytic Degradation of 4- Nitrophenol on TiO2-MWCNT/Ti Electrode Using Multivariate Cure Resolution-Alternating Least Squares Method - Fatemeh Chitgaran; S. Maryam Sajjadi; Farideh Nabizadeh Chianeh; Javad Feizy (شیمی کاربردی روز, 2023)
In this study, TiO2-MWCNT nanoparticles were deposited on Ti electrode by electrophoretic deposition (EPD) method. Scanning electron microscopy method verified that TiO2-MWCNT were deposited on Ti homogeneously. The Modified electrode was employed as an anode for the degradation of 4-nitorohenol pollutant that monitored spectroscopically. The degradation process of this contaminant was investigated by photo-catalytic (PC), electro-chemical (EC) and photo-electro-catalytic (PEC) methods. The results revealed that PC process was highly slow and there was signal overlapping for the components involved in two other processes, a fact which prevents extracting the kinetic profile of 4-nitrophenol. To overcome this problem, it was proposed to use multivariate cure resolution-alternating least squares (MCR-ALS) method for data analysis. Finally, the pure kinetic and spectral profiles of components were obtained using MCR-ALS method and the efficiencies of the applied degradation methods are ranked as follows: PEC>EC>PC.